2020
DOI: 10.2486/indhealth.2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and associated factors among Japanese nursery school and kindergarten teachers: a cross-sectional study

Abstract: The understaffing of nursery schools and kindergartens and the increasing workload of childcare workers are becoming significant issues in Japan. In this study, a cross-sectional survey was conducted to investigate the stress experienced by childcare workers and its antecedents. We distributed 2,640 questionnaires to childcare workers in Miyagi prefecture, obtaining a response rate of 51.9% (n = 1,370). Finally, 1,210 valid questionnaires were used in the analysis. As a stress indicator, psychological distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
4
8
1
Order By: Relevance
“…We also surveyed work-related social support as a covariate of psychologic distress and found that supervisor support was 11.8 and coworker support was 11.9. These values are comparable with those reported for childcare workers (supervisor support: 11.8; coworker support: 12.1) 4 and slightly higher than female government workers (supervisor support: 10.5; coworker support: 11.0) 12 in previous studies. Additionally, in many cases, there is only one dietitian assigned to a workplace or the dietitians' supervisors are from a different profession.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We also surveyed work-related social support as a covariate of psychologic distress and found that supervisor support was 11.8 and coworker support was 11.9. These values are comparable with those reported for childcare workers (supervisor support: 11.8; coworker support: 12.1) 4 and slightly higher than female government workers (supervisor support: 10.5; coworker support: 11.0) 12 in previous studies. Additionally, in many cases, there is only one dietitian assigned to a workplace or the dietitians' supervisors are from a different profession.…”
Section: Discussionsupporting
confidence: 89%
“…In previous surveys, the mean ER ratios for other occupations were reported to be 0.5 for 1000 female office employees, 29 0.7 for 2208 female specialists, 29 0.8 for 348 nurses, 7 0.93 for 1210 childcare workers, 4 and 1.38 for 342 eldercare workers 8 in Japan. Compared with other occupations, we found the mean ER ratio of dietitians to be higher than that of female office employees and specialists, 29 lower than that of childcare 4 and eldercare workers, 8 and comparable to nurses. 7 However, this comparison was not adjusted for gender, age, and other covariates.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…While psychological distress has been studied among samples in various occupations ( 39 42 ), to the authors' knowledge, no studies have investigated psychological distress among non-profit employees specifically, despite the growth of non-profit sectors around the globe [e.g., ( 43 , 44 )] and especially in China ( 17 , 18 ). Thus, we seek to fill this gap in the literature by examining psychological distress among Chinese non-profit employees, including its relations with JD-R and their underlying mechanism.…”
Section: The Jd-r Model Burnout and Psychological Distressmentioning
confidence: 99%